MAT081: Mathematics I (Basic) / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (2023)
This course consists of basic topics covered in KBSM level. The topics are number system, straight lines, solving equations (linear and quadratic), trigonometry and introductions to differentiation and integration. This course will prepare them for a diploma program.